A case series illustrating the implementation of a novel tele-neuropsychology service model during COVID-19 for children with complex medical and neurodevelopmental conditions: A companion to Pritchard et al., 2020. Issue 1 (2nd January 2021) - Peterson, Rachel K.; Ludwig, Natasha N.; Jashar, Dasal Tenzin
Abstract: Objective: Despite a movement toward tele-based clinical services in other healthcare domains, implementation of these services within neuropsychology, particularly with pediatric populations, is limited. With the onset of social distancing due to COVID-19, the field of pediatric neuropsychology is encouraged to consider the utility of non-traditional, tele-neuropsychological assessments. In order to accommodate ongoing service needs for medically and neurodevelopmentally complex children, a novel three-tiered telehealth service model of care was developed and implemented in a large pediatric outpatient neuro/psychological clinic within an academic medical center. Method: In this article, we provide case examples that illustrate the clinical implementation of this three-tiered telehealth service model of care for serving children during this uncertain time. Conclusion: The primary aim of this article is to provide examples outlining how clinical service decisions were made in the application of this three-tiered model for children with complex medical and neurodevelopmental histories. This article is intended to serve as a guide for other pediatric neuropsychology providers considering tele-neuropsychological services for complex pediatric patients during social distancing.